Enhancing the decision-making process when considering artificial nutrition in advanced dementia care. (2nd May 2019) - De, Diana; Thomas, Carol
Abstract : Background: Nutritional problems often manifest during late-stage dementia, and some families may request to instigate artificial nutrition and hydration (ANH) therapies. In the US, an estimated one-third of nursing home patients with a severe cognitive impairment have artificial feeding tubes inserted. Fear that a relative could experience extreme hunger or thirst if they are not mechanically fed tends to be the main driver behind family's requests to implement artificial or enteral feeding methods. In contrast, artificial hydration is rarely given to older people with dementia in the UK and this practice of non-intervention tends to apply across all healthcare and hospice type environments. Aim: This literature review aims to evaluate the evidence to support the use and non-use of ANH. Method: A literature review was undertaken to examine the evidence around ANH for patients with dementia to offer support to families or carers contemplating feeding choices. Conclusion: This paper challenges the implementation of invasive ANH worldwide. It highlights how resorting to ANH does not necessarily lead to improvements in comfort, survival or wound healing. The risk of aspiration does not appear to significantly alter either.